Terrorism : a philosophical investigation - Primoratz, Igor. (Cambridge, UK : Polity, 2013)
'This is the first comprehensive study of the core philosophical questions posed by terrorism such as: How should we define it? Is it morally distinctive? Can it be morally justified? Igor Primoratz seeks to overcome relativism and the double standards that often plague debates about terrorism. He investigates the main ethical approaches to terrorism: in terms of its consequences, rights and justice,'supreme emergency,' and the collective responsibility of citizens. The book provides a rigorous, yet accessible analysis of a range of moral positions, from the acceptance of terrorism when its consequences are good on balance to its absolute rejection. Primoratz argues that terrorism is almost absolutely wrong. It may be morally justified only when an entire people is facing a true moral disaster, and this should be understood in a highly restrictive way. Conceptual analysis and normative arguments about the practice of terrorism are complemented by case studies of the terror bombing of German cities in World War II and the role of terrorism in the Israeli-Palestinian conflict. Terrorism: A Philosophical Investigation will be essential reading for researchers and students of philosophy and politics, as well as for the general reader seeking to understand and evaluate acts and campaigns of terrorism.'--P. [4] of cover.
Includes bibliographical references (p. [180]-188) and index.
Keywords: Terrorism -- Philosophy